Simulator performance differences between experienced and novice bus drivers. - Dorn, Lisa; Stannard, Jenny (University of Roma TRE, 2006)
In order to combat the problem of novice bus driver risk, a bus simulator was developed to improve decision-making at hazards that are most often associated with bus crashes. If the simulator is capable of discriminating between novice and experienced bus drivers then it can be argued that it is a valid tool for bus driver training to improve road safety. The purpose of this study then is to investigate whether there are significant differences between experienced and novice bus driver performance. Twelve novice bus drivers with 2-3weeks of driver training, and twelve experienced drivers who had held their PCV (Public Commercial Vehicle) license for at least three years were asked to drive a simulated bus route. Participants drove for approximately 15 minutes encountering three major hazardous locations for bus driving, namely, layby bus stops, parallel bus stops and right hand junctions. At these locations, parameters measured were speed, acceleration, position, steering and braking. The results showed that experienced drivers demonstrated greater caution but more confident behavioural strategies at layby and parallel bus stops. At right hand junctions, experienced drivers drove slower and further away from the kerb and used the brake significantly more often than novice bus drivers did. Results are discussed with reference to the use of a driving simulator for novice bus driver training.
Keywords: bus drivers; driver training; novice drivers; experience drivers